Lycorine protects motor neurons against TDP-43 proteinopathy-induced degeneration in cross-species models with amyotrophic lateral sclerosis - Jing Wen; Yunhao Li; Yanzhu Qin; Lingli Yan; Ke Zhang; Ang Li; Ziying Wang; Feng Yu; Jianheng Lai; Wei Yang; Yong U. Liu; Dajiang Qin; et al. (Elsevier, 2024)
Aggregation of TAR-DNA binding protein-43 (TDP-43) is a pathological feature present in nearly 97 % cases of amyotrophic lateral sclerosis (ALS), making it an attractive target for pathogenic studies and drug screening. Here, we have performed a high-throughput screening of 1500 compounds from a natural product library and identified that lycorine, a naturally occurring alkaloid, significantly decreases the level of TDP-43A315T in a cellular model. We further demonstrate that lycorine reduces the level of TDP-43A315T both through inhibiting its synthesis and by promoting its degradation by the ubiquitin-proteasome system (UPS). Importantly, treatment with lycorine significantly attenuates TDP-43 proteinopathy and improves functional recovery in TDP-43A315T-expressing Caenorhabditis elegans and mouse models. These findings suggest that lycorine is a promising lead compound that has therapeutic potential for ALS.